Application of swarm intelligence algorithms in solving the inverse heat conduction problem - Hetmaniok, Edyta; Słota, Damian; Zielonka, Adam (Computer Assisted Methods in Engineering and Science, 2012)
In the paper a proposal of using selected swarm intelligence algorithms for solving the inverse heat conduction problem is presented. The analyzed problem consists in reconstructing temperature distribution in the given domain and the form of heat transfer coefficient appearing in the boundary condition of the third kind. The investigated approaches are based on the Artificial Bee Colony algorithm and the Ant Colony Optimization algorithm, the efficiency of which are examined and compared.